Eksistensi Rupbasan Dalam Pengelolaan Benda Sitaan Kapal Guna Mendukung Perlindungan Hukum Pada Proses Penegakan Hukum Di Laut - Soniady Drajat Sadarisman; Tasween Tasween; Hasbi Hasan (Universitas Jayabaya, 2016)
Law enforcement at sea, seized ships that had been appropriated after stipulation of confiscation by a head of district court, have to be placed in the safe house as well. Though ideally the safe house is established in every district or municipality, up to the recent time the fact is that has not been able to realize yet. With regard to law enforcement in the sea, the absence of Rupbasan. It is particularly in the remote area and outermost islands have become an issue for investigators as they cannot keep their confiscated goods in Rupbasan. Normative law research is applied as a method in this research as an effort to obtain necessary data which related to the issue. The research found the fact not only that in the law enforcement at sea, confiscated objects are not to be kept in Rupbasan since it has not built yet in all districts and municipalities, but also particularly because to keep the ship in Rupbasan is not feasible. These acts had been found in every stage of law enforcement which are the investigation, prosecution, education, and execution. The way how to treat this matter has not been regulated yet in The Criminal Code Procedure (KUHAP), Government Regulation Number 27 in 1983 and other regulations which means an absence of law. It is really necessary all of that has to be regulated by new form of regulation.